A candidate‐SNP retrospective cohort study for fracture risk in Japanese Thoroughbred racehorses. (14th October 2019) - Tozaki, T.; Kusano, K.; Ishikawa, Y.; Kushiro, A.; Nomura, M.; Kikuchi, M.; Kakoi, H.; Hirota, K.; Miyake, T.; Hill, E. W.; Nagata, S.
Summary: Fractures are medical conditions that compromise the athletic potential of horses and/or the safety of jockeys. Therefore, the reduction of fracture risk is an important horse and human welfare issue. The present study used molecular genetic approaches to determine the effect of genetic risk for fracture at four candidate SNPs spanning the myostatin ( MSTN ) gene on horse chromosome 18. Among the 3706 Japanese Thoroughbred racehorses, 1089 (29.4%) had experienced fractures in their athletic life, indicating the common occurrence of this injury in Thoroughbreds. In the case/control association study, fractures of the carpus (carpal bones and distal radius) were statistically associated with g.65809482T/C ( P  =   1.17 x 10 ‐8 ), g.65868604G/T ( P  =   2.66 x 10 ‐9 ), and g.66493737C/T ( P  =   6.41 x 10 ‐8 ). In the retrospective cohort study using 1710 racehorses born in 2000, the relative risk (RR) was highest for male horses at g.65868604G/T, based on the dominant allele risk model (RR = 2.251, 95% confidence interval 1.407–3.604, P  =   0.00041), and for female horses at g.65868604G/T, based on the recessive allele risk model (RR = 2.313, 95% confidence interval 1.380–3.877, P  =   0.00163). Considering the association of these SNPs with racing performance traits such as speed, these genotypes may affect the occurrence of carpus fractures in Japanese Thoroughbred racehorses as a consequence of the non‐genetic influence of the genotype on the distance and/or intensity of racing and training. The genetic information presented here may contribute to the development of strategic training programs and racing plans for racehorses that improve their health and welfare.